Effect of Oral Isotretinoin Treatment on Retinal Nerve Fiber Layer Thickness - Ucak, Haydar; Aykut, Veysel; Ozturk, Savas; Cicek, Demet; Erden, Ilker; Demir, Betul (B C Decker Inc, 2014)
Background: Oral isotretinoin treatment can cause ocular side effects. Objective: This study was performed to detect possible toxic effects of oral isotretinoin treatment on the retinal nerve fiber layer (RNFL) and ganglion cell layer (GCL). Methods: The study population consisted of 54 eyes of 27 patients with nodulocystic acne who used oral isotretinoin (Roaccutane) treatment. Macular GCL and peripapillary RNFL thickness measurements were performed using spectral domain optical coherence tomography (OCT) before and after therapy. Results: Before and after treatment, a complete ophthalmologic examination was normal in all eyes. However, posttreatment lower temporal (TL) values were significantly lower (76.80 +/- 16.31) than pretreatment TL values (84.96 +/- 24.83) (p = .02). There was no statistically significant difference in the other OCT values, upper temporal, superotemporal, superonasal, upper nasal, lower nasal, inferonasal, and inferotemporal (p = .35, p = .40, p = .56, p = .95, p = .94, p = .93, p = .61, respectively). Also, there was no statistically significant difference between the right and left eyes and between genders for all parameters (p > .05). Conclusion: The use of oral isotretinoin treatment has increased in recent years. In addition, oral isotretinoin treatment has a broad adverse effect potential on the ocular system. The measurement of RNFL thickness, especially TL thickness, by OCT may be useful for detecting the possible toxic effect of oral isotretinoin therapy on RNFL.
Keywords: Optical Coherence Tomography; Adverse Ocular Reactions; Acitretin Therapy; Neuropathy; Acid; Chloroquine; Retinoids; Glaucoma; Eyes